Strategi Unilever dalam Dinamika Politik Ekonomi Global Tahun 2023-2025: Adaptasi Korporasi Multinasional terhadap Kebijakan dan Kepentingan Negara - Fadilah Affwa; Nasywa Aisyiah Hilda Jannati; Shafa Kamila Khairunnisa; Tiara Witaloka; Septianis Afipah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines Unilever’s strategic responses to global political economy dynamics during the 2023-2025 period by positioning multinational corporations as non-state actors that interact directly with state policies and national interests. The research adopts a qualitative descriptive-analytical approach, drawing on secondary data sources including official corporate reports, state policy documents, and scholarly literature on international political economy. The findings indicate that geopolitical fragmentation, the strengthening of national policy frameworks, and the politicization of energy, food security, and labor issues have collectively shaped the strategic environment influencing Unilever’s decision-making processes. In response, the company has implemented supply chain diversification, reinforced local production capacities, ensured compliance with national regulations, and strategically managed its relationships with government institutions. The study further reveals that Unilever does not merely adapt to state policies but also contributes to shaping global governance practices and international standards. These findings underscore the necessity of employing a political economy approach to analyze multinational corporate strategies in order to comprehensively understand power relations, national interests, and evolving global dynamics.